The influence of family communication in developing Muslim personality: an overview of family communication patterns theory / Aini Faezah Ramlan...[et.al] - Ramlan, Aini Faezah; Suyurno, S Salahudin; Sharipp, Muhammad Taufik; Ridzuan, Abdul Rauf; Abd Ghani, Siti Nur Farrah Faadiah (Academy of Contemporary Islamic Studies, 2018)
Family communication is essential to create positive environment in a family. This type of communication involves on the interaction among the family members such as between the parents with the children and vice versa. The study of family communication is attributed to the understanding towards the factor of social problems among the youths, conficts in marriage and other consequences of degrading in terms of human interpersonal communication. Family communication play significant role in developing youth personality. Islam emphasizes the role of parents in nurturing their children to have Muslim identity that become an asset for the ummah. Muslim personality is the source of goodness and constructive elements in the society. Positive interactive between parents and adolescents in families would lessen towards health risk behaviors that contribute to unintentional injuries, tobacco use, alcohol and other drug use, sexual behaviors that contribute to unintended pregnancy and others. However, nurturing children according to the Islamic values in modern-globalized environment is quite challenging. Family communication and interaction is lessen due to the increasing usage of technology. Research findings on deliquencies behaviors among Malay youths showed that family institutions have contributed to the increasing rate of social ills in societies (Azizi Yahya & Badrulzaman Baharom,(nd). This article will highlight the influence of family communication in developing ummah by reviewing Family Communication Pattern Theory.This theory shows consistency with Islamic teachings the role of parents as agents of religious socialization in developing Muslim personality.